Stem Cell-Based Therapies in Hearing Loss - He, Zuhong; Ding, Yanyan; Mu, Yurong; Xu, Xiaoxiang; Kong, Weijia; Chai, Renjie; Chen, Xiong (Frontiers in Cell and Developmental Biology, 2021)
In recent years, neural stem cell transplantation has received widespread attention as a new treatment method for supplementing specific cells damaged by disease, such as neurodegenerative diseases. A number of studies have proved that the transplantation of neural stem cells in multiple organs has an important therapeutic effect on activation and regeneration of cells, and restore damaged neurons. This article describes the methods for inducing the differentiation of endogenous and exogenous stem cells, the implantation operation and regulation of exogenous stem cells after implanted into the inner ear, and it elaborates the relevant signal pathways of stem cells in the inner ear, as well as the clinical application of various new materials. At present, stem cell therapy still has limitations, but the role of this technology in the treatment of hearing diseases has been widely recognized. With the development of related research, stem cell therapy will play a greater role in the treatment of diseases related to the inner ear.